THE INFLUENCE OF SOCIAL MEDIA MARKETING ON THE BRAND EQUTY OF PACKAGED FRUIT JUICE BEVERAGES IN THE COMMUNITY OF LHOKSEUMAWE CITY - Muhammad Fariz Pratama; Rusydi Abubakar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to analyze the influence of social media marketing on the brand equity of packaged fruit juice beverages among the community in Lhokseumawe City. Data for this research were collected through a survey method using a questionnaire as the data collection instrument. The respondents in this study were 100 residents of Lhokseumawe City. This research employed a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The results of the study indicate that, partially, entertainment has a positive and significant effect on the brand equity of packaged fruit juice beverages among the community in Lhokseumawe City. Customization has a positive and significant effect on the brand equity of packaged fruit juice beverages among the community in Lhokseumawe City. Interaction has a positive and significant effect on the brand equity of packaged fruit juice beverages among the community in Lhokseumawe City. E-WOM has a positive and significant effect on the brand equity of packaged fruit juice beverages among the community in Lhokseumawe City. Trendiness has a positive and significant effect on the brand equity of packaged fruit juice beverages among the community in Lhokseumawe City.